Transformação de Möbius - Santos, Marcus Vinicio de Jesus (2016)
The aim of this work is the study of arbitrary mobius transformations by means of simple complex transformations, namely: the Translation, the Rotation, the Homotetia (Contraction and Dilatation) and Inversion. The results obtained were applied in circles and straight line. At the end, we give the the alternative of studying mobius transformations via matrices.